Will the Stars Sing on the Last Day? Cosmology and Eschatology - Root, Michael (International journal of systematic theology, 2025)
Changes in the scientific picture of the origin and destiny of the physical universe present particular challenges to Christian eschatology. Both the great expansion of our picture of the size and age of the universe and the recent perception of an inexorable progression of the universe toward heat death in the far future alter the secular understanding of the universe with which Christian theology engages. In this essay, these challenges are considered in relation to how the theologian is to understand the eschatological role of physical objects far removed from interaction with humanity, for example, distant stars. Anthropocentric understandings of their role become implausible in light of recent changes in cosmology. This essay explores the traditional doctrine of bodily resurrection as a potential key to understanding the eschatological significance of stars. The insistence that the risen body is both radically transformed and yet numerically identical with the present body provides some parameters for understanding the nature of an eschatologically transformed universe and how its flourishing might be a witness to the glory of God.